2022
DOI: 10.1007/s10696-022-09462-x
|View full text |Cite
|
Sign up to set email alerts
|

Robust berth scheduling using machine learning for vessel arrival time prediction

Abstract: In this work, the potentials of data-driven optimization for the well-known berth allocation problem are studied. The aim of robust berth scheduling is to derive conflict-free vessel assignments at the quay of a terminal, taking into account uncertainty regarding the actual vessel arrival times which may result from external influences as, e.g., cross wind and sea current. In order to achieve robustness, four different Machine Learning methods-from linear regression to an artificial neural network-are employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 66 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…This study considers continuous berthing layout and dynamic vessel arrival along with a robust optimization approach based on dynamic time buffers. Another study presented in [83] also employs ML models (namely, linear regression, k‐nearest neighbour, decision tree regressor, and artificial neural networks) for actual ATP of vessels, and then an exact optimization method is utilized to solve the continuous BAP. Based on extensive simulations, it is concluded that ML‐based ATP of vessels could improve the optimization results, as accurate prediction helps a lot to minimize uncertainty in vessel arrivals.…”
Section: Current Literature On Stand‐alone Bapmentioning
confidence: 99%
“…This study considers continuous berthing layout and dynamic vessel arrival along with a robust optimization approach based on dynamic time buffers. Another study presented in [83] also employs ML models (namely, linear regression, k‐nearest neighbour, decision tree regressor, and artificial neural networks) for actual ATP of vessels, and then an exact optimization method is utilized to solve the continuous BAP. Based on extensive simulations, it is concluded that ML‐based ATP of vessels could improve the optimization results, as accurate prediction helps a lot to minimize uncertainty in vessel arrivals.…”
Section: Current Literature On Stand‐alone Bapmentioning
confidence: 99%
“…The objective function of the [PSP] is given by constraint (45), aiming to minimize the RC. Constraints ( 50) and ( 51) establish the relationship between the vessel berthing and the variable β i b,d,t in the master problem.…”
Section: Pricing Sub-problemmentioning
confidence: 99%